An Overview of Contemporary Corporate Governance in China: An Interpretation and Analysis - Trant, Philippa Jane (2006)
Effective corporate governance has become imperative for companies internationally. This thesis draws on the contemporary issues involved with China's corporate governance situation, particularly exploring whether its economic and political history and its unique cultural traits have influenced the current effectiveness of its system. The problems with China's current corporate governance system and informed speculative solutions will be reviewed in turn. Even though China has adopted features similar to both the Anglo-American Model and the German-Japanese Model of corporate governance, it can be seen that China will have to adopt its own model that is path-dependent and in tune with its characteristics. However, in order for China to become a key player in the global economy and to continuously attract international investment, the importance of a sound corporate governance system is essential.